Pandemic and Global Civil Society: Shifting the Power Balance Towards the State? - Md. Kowsar (Global Local Interactions: Journal of International Relations, 2022)
This paper discusses about the impacts of the Covid-19 pandemic on the global civil society. It mainly focuses on how the pandemic is reducing the power of the global civil society in international politics while it is reinforcing the power of the state. Prominent theories of international relations, such as Realism, liberalism and constructivism assert the primacy of state in international politics while giving little importance to global civil society as an actor. However, the advocates of global civil society claim that, currently, global civil society is a much important actor in international politics. They also assert that states are gradually losing power to the global civil society. This paper argues that the pandemic has reversed this trend and shifted the power balance towards the state. Using the realist critic this paper argues that the pandemic has impacted international politics in a way that is reinforcing the primacy of the state and weakening the global civil society. As a result, global civil society is losing their ability to counter the state in world politics and are being forced to comply with the interests of the state.